Two new species of the millipede family Trichopolydesmidae from Bahia state, northeastern Brazil, including a remarkable threatened troglobiont (Diplopoda, Polydesmida) - Golovatch, Sergei I.; Gallo, Jéssica S.; Bichuette, Maria E. (Zootaxa, 2022)
Phaneromerium troglopterygotum sp. nov. and Moojenodesmus schubarti sp. nov. are described from Bahia state, northeastern Brazil. The former species is a remarkable troglobiont relict endemic to a single limestone cave from the Serra do Ramalho karst area; it shows some clear-cut troglomorphic traits, and particular biology and ecology. The latter species occurs close to limestone outcrops of the Serra do Iuiu karst area. Both regions generally support a typical dry tropical climate, but the cave and outcrop habitats represent sites with high humidity, this being essential for the survival of these and other species.